Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.3390/environments2020167
|View full text |Cite
|
Sign up to set email alerts
|

Harvesting Effects on Species Composition and Distribution of Cover Attributes in Mixed Native Warm-Season Grass Stands

Abstract: Managing grasslands for forage and ground-nesting bird habitat requires appropriate defoliation strategies. Subsequent early-summer species composition in mixed stands of native warm-season grasses (Indiangrass (IG, Sorghastrum nutans), big bluestem (BB, Andropogon gerardii) and little bluestem (LB, Schizachyrium scoparium)) responding to harvest intervals (treatments, 30, 40, 60, 90 or 120 d) and durations (years in production) was assessed. Over three years, phased May harvestings were initiated on sets of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Other experiments have produced opposite results and demonstrated that most tall herbs do not tolerate mowing pressure (Mitchley and Willems 1995;Valkó et al 2012;Temu et al 2015). According to Fynn et al (2004), early cutting of bud tops reduces the flowering and fruiting of tall perennials and eliminates them slowly from phytocenoses.…”
Section: Discussionmentioning
confidence: 99%
“…Other experiments have produced opposite results and demonstrated that most tall herbs do not tolerate mowing pressure (Mitchley and Willems 1995;Valkó et al 2012;Temu et al 2015). According to Fynn et al (2004), early cutting of bud tops reduces the flowering and fruiting of tall perennials and eliminates them slowly from phytocenoses.…”
Section: Discussionmentioning
confidence: 99%
“…For managed defoliation to fulfil the set objective(s), relevant plant responses to the treatments are usually monitored through changes in species composition-numbers, spatial distribution, growth performance, stand thickness, structural uniformity, etc. [6,7,9,10]. While species composition and structural uniformity could be the focus for ecosystem services and conservation-related defoliation management, forage production responses will include regrowth performance and stand thickness.…”
Section: Introductionmentioning
confidence: 99%
“…Usually, plant species differ in their abilities to compensate for defoliation-imposed tissue damages (Dawson et al, 2000) as reflected in respective regrowth rates (van Staalduinen and Anten, 2005). In mixed stands, such differences may lead to subsequent changes in forage biomass (Temu et al, 2014), sward structure, and/species composition (Temu et al, 2015). Owing to differences, in species' ability to restore lost photosynthetic capacities, recovery growths often result in under/overcompensation of preceding tissue damages.…”
Section: Species Forage Biomassmentioning
confidence: 99%